2012
DOI: 10.1152/ajpendo.00360.2011
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary running exercise prevents β-cell failure in susceptible islets of the Zucker diabetic fatty rat

Abstract: Physical activity improves glycemic control in type 2 diabetes (T2D), but its contribution to preserving β-cell function is uncertain. We evaluated the role of physical activity on β-cell secretory function and glycerolipid/fatty acid (GL/FA) cycling in male Zucker diabetic fatty (ZDF) rats. Six-week-old ZDF rats engaged in voluntary running for 6 wk (ZDF-A). Inactive Zucker lean and ZDF (ZDF-I) rats served as controls. ZDF-I rats displayed progressive hyperglycemia with β-cell failure evidenced by falling ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 60 publications
3
30
0
1
Order By: Relevance
“…Therefore, our results indicated a more direct contribution of PA in preserving β-cell function. Moreover, our findings are consistent with the results of a recent study in rats, which demonstrated that voluntary exercise was beneficial for sustaining β-cell compensation without preventing dyslipidemia or obesity (35). One possible mechanism for such an effect would be mitigation of the adverse metabolic effects of obesity.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, our results indicated a more direct contribution of PA in preserving β-cell function. Moreover, our findings are consistent with the results of a recent study in rats, which demonstrated that voluntary exercise was beneficial for sustaining β-cell compensation without preventing dyslipidemia or obesity (35). One possible mechanism for such an effect would be mitigation of the adverse metabolic effects of obesity.…”
Section: Discussionsupporting
confidence: 92%
“…Improvement in Matsuda index and reduced insulin levels with intermittent walking is consistent with previous observations of the preservation of beta-cell function by conservation of pancreatic insulin stores with physical activity. 25 Importantly, the lowering of glucose and insulin with intermittent walking was most distinguishable in the postprandial periods. Postprandial hyperglycaemia may be a better predictor of CVD mortality than fasting hyperglycaemia 26 and blunting of postprandial glucose is shown to reduce intima media thickness, oxidative stress, inflammation and endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise maintained or enhanced beta cell function in older obese individuals, with improved beta cell function correlating with reduced glucose concentrations (Malin and Kirwan, 2012). In the ZDF rat, voluntary running prevented the development of diabetes despite continuing hyperphagia, obesity, and hyperlipidemia (Delghingaro-Augusto et al, 2012). Compensatory insulin secretion was preserved and hyperglycemia prevented by exercise was characterized by enhanced insulin secretion per islet and the prevention of severe depletion of islet insulin stores (Delghingaro-Augusto et al, 2012).…”
Section: Beta Cell Preservationmentioning
confidence: 99%
“…In the ZDF rat, voluntary running prevented the development of diabetes despite continuing hyperphagia, obesity, and hyperlipidemia (Delghingaro-Augusto et al, 2012). Compensatory insulin secretion was preserved and hyperglycemia prevented by exercise was characterized by enhanced insulin secretion per islet and the prevention of severe depletion of islet insulin stores (Delghingaro-Augusto et al, 2012). Frequent exercise and adopting a healthy diet is a strategy to improve diabetic outcomes, particularly in pre-diabetic states such as obesity and/or insulin resistance and beta cell dysfunction.…”
Section: Beta Cell Preservationmentioning
confidence: 99%